Cube-based diffusion algorithm - Zschiegner, Stephan; Russ, Stefanie; Bunde, Armin; Kärger, Jörg (Diffusion Fundamentals, 2007)
We study molecular diffusion in (linear) nanopores with different types of roughness in the so-called Knudsen regime. Knudsen diffusion represents the limiting case of molecular diffusion in pores, where mutual encounters of the molecules within the free pore space may be neglected and the time of flight between subsequent collisions with the pore walls significantly exceeds the interaction time between the pore walls and the molecules. In this paper we present in full detail the algorithm, which we used in our previous studies, where we showed complete equivalence of self- (or tracer-) and transport diffusion.